Human activities to meet the diverse needs in the use of physical exercises - the basis of the mechanism of self-development of physical culture - Sutula Vasilij Afanas'evich (Kharkov National Pedagogical University, 2011)
The features of social activities to meet the needs of people. A scheme for self-regulatory process of the people to respond to biological, social and biosocial needs. It is shown that the diversity of human needs is divided into three groups: biologically and socially determined needs, the needs-based biosocial nature. It is shown that in a society based on competitive interaction of people, a system of relations. These relationships are the basis for the development of physical culture. It is noted that this process acts as a public evaluation mechanism for the selection of the variety of social phenomena. At the heart of the process of competitive interactions between them reflects the process of emergence and development of socially significant events. These phenomena are different forms of social manifestations of physical culture (physical education, sport, physical recreation, physical rehabilitation and adaptive physical education).